Organizational context, structure, and performance of plant turnaround maintenance in Malaysian process based industries / Zulkipli Ghazali - Ghazali, Zulkipli (2010)
Plant turnaround maintenance is a crucial asset management that is practiced in large process-based industries. The unprecedented large and expensive maintenance event is carried out to revitalize, maintain, and improve the plant facilities for optimal and efficient performance. The event is characterized by a multi-facetted business process comprising engineering, business, and organization. Typical problems that are linked to the dismal performance of the plant turnaround maintenance include schedule slippage, work scope growth, cost over run, concerns on regulatory compliance, inadequate resources, and startup problems. These depictions imply that the turnaround maintenance event requires efficient organization, coordination, and control of the turnaround organizational resources to ensure its successful implementation. The present study examines the effect of congruent relationship between plant technology, organizational size, and structuring processes on the performance of plant turnaround maintenance of process-based industries in Malaysia. The study was based on quantitative data collected from 58 companies using questionnaire-aided survey. A research framework is developed and 25 research hypotheses are put forth, which suggest the relationship of plant technology, organizational size, structuring processes, and organizational performance of turnaround maintenance.